Cyber resilience in combating ransomware attacks: A psychological case study perspective on the hospitality industry - Cahyandari, Yenika Putri; Chusniyah, Tutut; Setiyowati, Ninik (Institut Agama Islam Negeri Langsa, 2024)
This paper studies the drivers that have a significant impact on organizational resilience in terms of ransomware attacks in the hospitality industry of Indonesia, with a particular focus on hotels operating in Bali. The interviews with IT managers in two of the most important hotels were conducted using in-depth interviews. They showed that the ransomware attacks caused severe operational disturbances and a loss of consumer confidence. Despite these, several proactive measures have been put in place by the hotels, and this has emanated through the strong leadership from the senior management to upgrade cybersecurity infrastructure and to instigate staff awareness programs. The findings pinpoint budget limitations and inadequate training, which align with the existing literature, as some of the important obstacles. The work underlines the desperate need for adaptive strategies in cybersecurity and develops an understanding that a collective organizational commitment is required toward sensitive data protection and good reputation building. Indeed, the research points out that creating security awareness among all employees would genuinely enhance the culture of cybersecurity and resilience. Collaboration between industry players and governmental bodies may provide the required wherewithal and frameworks for building up strength with which the ransomware threat could be tackled effectively. Given the practical recommendations, it might be useful to consider how to make the hospitality industry resilient in the case of ransomware attacks